(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
English anxiety is a significant difficulty to the effective classroom communication in such circumstances where English is not the native talent like in Nigeria. The article speaks about English speaking anxiety and communication in classroom among the undergraduates in Enugu State, Nigeria and employs primary data collection method using mixed methods approach. According to the surveys and the discussions on anxiety during focus groups with 450 students in three universities, the study identifies the impacts of anxiety on participation and interaction as well as the performance of students in the English-median classrooms. The findings indicate that, speaking anxiety causes low levels of involvement and engagement in the verbal activity with gender, academic discipline and an experience previously having had with English as a moderating factor. The analysis is sealing the holes in the local researches because the author focuses on the Nigerian context where the English language is the primary academic tool even though there are language disparities. Individualized pedagogic practices and institutional support to eliminate anxiety and ensure inclusive learning environments are implied. This paper assists in the understanding of the socio-psychological processes when language is administered in the institutions of education at the higher levels and offers a vantage point pragmatically to the teachers, as well as in the policy makers.